DEVELOPMENT OF ARTIFICIAL INTELLIGENCE-BASED 3D VISUALIZATION AND EARLY DIAGNOSIS SYSTEM FOR CARDIOVASCULAR DISEASES - Makhmudova , Sabina; Tastanova , Saida (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article discusses the theoretical and practical foundations of a system for early detection and 3D visualization of cardiovascular diseases using artificial intelligence (AI) technologies. The system’s diagnostic effectiveness, disease prevention, and the importance of developing individual treatment strategies for patients are demonstrated.